2005
DOI: 10.1016/j.ccr.2004.11.025
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1-stathmin interaction influences sarcoma cell migration and invasion

Abstract: Emerging evidences suggest that cyclin-dependent kinase inhibitors (CKIs) can regulate cellular functions other than cell cycle progression, such as differentiation and migration. Here, we report that cytoplasmic expression of p27(kip1) affects microtubule (MT) stability following cell adhesion on extracellular matrix (ECM) constituents. This p27(kip1) activity is due to its ability to bind and impair the function of the MT-destabilizing protein stathmin. Accordingly, upregulation of p27(kip1) or downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
354
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(378 citation statements)
references
References 50 publications
22
354
0
Order By: Relevance
“…Previous studies have established an association between STMN1 and p27. Baldassarre et al (16) reported that STMN1 binds to p27 in the cytoplasm, and that sarcoma cells with high expression levels of STMN1 and low expression levels of p27 demonstrate increased proliferation and invasion (16). In our previous report, a similar association was found between STMN1 and p27 in extrahepatic cholangiocarcinoma, in which samples with high expression levels of STMN1 tended to have low expression levels of p27.…”
Section: Expression Of Stmn1/skp2 (N) -------------------------------supporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies have established an association between STMN1 and p27. Baldassarre et al (16) reported that STMN1 binds to p27 in the cytoplasm, and that sarcoma cells with high expression levels of STMN1 and low expression levels of p27 demonstrate increased proliferation and invasion (16). In our previous report, a similar association was found between STMN1 and p27 in extrahepatic cholangiocarcinoma, in which samples with high expression levels of STMN1 tended to have low expression levels of p27.…”
Section: Expression Of Stmn1/skp2 (N) -------------------------------supporting
confidence: 61%
“…Additionally, there is evidence to suggest that STMN1 regulates the function of p27, a cytoplasmic protein shown to regulate cell migration. For example, Baldassarre et al (16) reported that STMN1 binds to p27 in the cytoplasm of cancer cells and enhances their proliferation by suppressing p27 function. In our previous study, a similar association between STMN1 and p27 was found in the cytoplasm of extrahepatic cholangiocarcinoma cells, which resulted in suppressed proliferation by inhibiting the intranuclear transport of p27 (15).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Baldassarre et al proposed that stathmin might play a role in the migration and metastasis of sarcoma cells. Their studies suggested that p27 Kip1 binds to stathmin and impairs its function, thus abrogating the ability of sarcoma cells to migrate and invade (23). In the same study, they showed that high levels of stathmin expression and low levels of p27 Kip1 in vivo in human sarcoma correlate with the metastatic phenotype (23).…”
Section: Discussionmentioning
confidence: 97%
“…Their studies suggested that p27 Kip1 binds to stathmin and impairs its function, thus abrogating the ability of sarcoma cells to migrate and invade (23). In the same study, they showed that high levels of stathmin expression and low levels of p27 Kip1 in vivo in human sarcoma correlate with the metastatic phenotype (23). Thus, stathmin expression seems to be critically important in cancer as reflected by its distinct roles in cell division, angiogenesis, and tumor cell metastasis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation